Observation and simulation of chemically mediated searches in marine zooplankton - Spencer J. Franks; Clayton Vondriska; Peter Hinow; Paul C. Sikkel (PLoS ONE, 2025)
Chemical communication is one of the most important capabilities of zooplankton, yet it remains understudied. We report observations of marine parasitic isopods Gnathia marleyi and coral larvae Orbicella faveolata in an aquatic olfactometer where individuals can respond to chemical signals from host fish species and crustose coralline algae, respectively. We complement these observations with a gradient search model inspired by the theory of Braitenberg vehicles. The mathematical model allows the agent to switch between periods of motion and periods of rest, guided by the behavior of G. marleyi. We further implement a temporary coupling of the agent to the signal gradient, interspersed with periods of seemingly aimless wandering. We find a favorable comparison between the experimental and simulated trajectories. This study gives us further insight on the chemosensory behavior of ecologically important marine invertebrates using novel instrumentation and methodology and is the first to attempt to model the chemosensory behavior of these two groups of aquatic invertebrates. Further research should seek to observe and model their behavior in three-dimensional space.